A Comparative Analysis on the Accuracy of Special and Prefabricated Impression Trays Using Additional Silicone in a Laboratory Model - Ladan Jamshidy; Mohammad Macvandi (Wolters Kluwer Medknow Publications, 2019)
Introduction: Impression technique plays a pivotal role in fixed prosthodontic treatments; one of the main steps of impression is selection and preparation of an appropriate tray. Impression technique with insufficient accuracy causes distortions and complications that consequently result in treatment failure. The present study compares the impression accuracy of special and prefabricated trays in a laboratory model. This article compares the accuracy of special and prefabricated impression trays for achieving better impression and finally better crowns with good adaptation. Materials and Methods: In this study, a laboratory-fabricated resin model, resembling a mandibular first molar, was used on a dental arch and prepared by standard method for full crown restorations with a finish line of 1-mm depth and 3° to 4° convergence angle. Impression was made from a laboratory-fabricated resin model, 40 times with monophase medium-body polyvinyl siloxane in special trays and 40 times with putty and light-body polyvinyl siloxane using double-mix impression technique without spacer in prefabricated trays. To measure marginal gap, distance between the restoration margin and preparation finish line was vertically determined on each die in the mesial, distal, buccal, and lingual regions. Statistical analysis was performed and data were analyzed by SPSS 20 software using independent samples t-test. The data were significantly different at P < 0.05.Results: The mean value of special tray impression (72.72) was lower than that of prefabricated tray impression (91.27). No significant difference was observed between two techniques in the mesial and buccal regions (P > 0.05). However, a significant difference was reported between the techniques in the lingual and distal regions.Conclusion: The present study indicated a higher accuracy for the special tray impression than prefabricated tray impression.